Saucepans and Saints? The Sacred and the Mundane in Forest Landscapes. (2nd January 2018) - Everson, Paul; Stocker, David
ABSTRACT: This paper outlines one component of a multi-disciplinary AHRC project 'The Sacred Landscapes of Medieval Monasticism', running between 2019 and 2022 but rooted in existing long-term studies in Ceredigion (Wales) and Lincolnshire (England). It encapsulates several strands of landscape analysis undertaken over many years which form a basis for the Lincolnshire contribution to the AHRC project. After a superficial characterisation of 'forest' land in the English Midlands, particular attention is paid to the landscape context of certain religious houses, exploring their connections with the social performance and ritual of hunting. General conclusions about the character of monasteries in 'forest' land are used to review the monastic landscape of the Lincolnshire limewoods, a 'forest' area in the middle Witham valley. It is suggested that during the high middle ages a concentration of monasteries exploited the pre-existing rituality of a forest and chase landscape in order to establish their sacred authority in local contemporary perceptions. The paper thus identifies the part played by sacred significance in the landscape setting in establishing monastic identity, considerations often crowded-out of monastic studies by economic analyses, but which generate an alternative academic agenda for the subject to be addressed through the forthcoming project.